1994
DOI: 10.1104/pp.104.2.309
|View full text |Cite
|
Sign up to set email alerts
|

How Do Chemical Signals Work in Plants that Grow in Drying Soil?

Abstract: We have known for many years that the dehydration of plant cells can lead to accumulation of the plant growth regulator ABA. Application of this compound to well-watered plants mimics many of the effects of soil drymg on gene expression, physiology, growth, and development, making this compound a strong candidate for a role in the droughted plant. Dehydration of leaves can result in massive accumulations of ABA, and roots also synthesize the compound in increased amounts as they are exposed to drier and drier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
0
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(144 citation statements)
references
References 4 publications
4
132
0
8
Order By: Relevance
“…This is supported by the stronger negative correlation of soil moisture tension with g s than with Ψ L (R = −0.71 * and −0.30 ns , respectively). These findings are consistent with the previous studies of Bano et al (1993), Davies et al (1994), Dingkuhn et al (1999), and Liu et al (2003), all of them suggested a primary role for root signals in regulating g s and leaf growth in rice and other crops under water defi cit. Our data provide strong evidence for root-to-shoot communication in rice, whereby the portion of roots in drying soil wielded a regulatory function on leaves, but this function was gradually removed upon excision of the droughted roots.…”
Section: Evidence For Root-to-shoot Communication In Ricesupporting
confidence: 83%
See 2 more Smart Citations
“…This is supported by the stronger negative correlation of soil moisture tension with g s than with Ψ L (R = −0.71 * and −0.30 ns , respectively). These findings are consistent with the previous studies of Bano et al (1993), Davies et al (1994), Dingkuhn et al (1999), and Liu et al (2003), all of them suggested a primary role for root signals in regulating g s and leaf growth in rice and other crops under water defi cit. Our data provide strong evidence for root-to-shoot communication in rice, whereby the portion of roots in drying soil wielded a regulatory function on leaves, but this function was gradually removed upon excision of the droughted roots.…”
Section: Evidence For Root-to-shoot Communication In Ricesupporting
confidence: 83%
“…Accumulated evidence suggests that both chemical and hydraulic signals are operative and integrated in the regulation of leaf growth and stomatal conductance when plants are grown under drought stress (Davies et al, 1994;Comstock, 2002). Their relative importance is likely to depend on plant size and growth conditions (Tardieu and Davies, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional view is that stomatal conductance (g s ) is controlled chiefly via leaf water status. It now appears that stomata, at least of plants in drying soil, might also be regulated by root-toshoot movement of chemical factors (Zhang et al, 1987 ;Davies et al, 1994 ;Tardieu et al, 1996 ; to exert a predominant influence, with leaf water status acting to modify stomatal sensitivity to the chemical signal (Tardieu & Davies, 1993 ;. Strong correlations between g s and xylem sap [ABA] have been reported under many conditions for several species, including trees (e.g.…”
Section: mentioning
confidence: 99%
“…Consequently, the traditional view of leaf water potential as a measure of water stress in plants (i.e. hydraulic signals) was proposed to be abandoned (SINCLAIR & LUDLOW, 1985;PASSIOURA, 1988a), and chemical signals produced in the roots dominated the view on how plants sense a drying soil during the late 80's and early 90's (ZHANG & DAVIES, 1989;DAVIES & ZHANG, 1991;DAVIES et al, 1994). KRAMER (1988) criticized this view arguing that, at that time, plant physiologists had spent 50 years of progress in the understanding of plant water relations by shifting emphasis away from the soil to the shoots, and now, plant physiologists would have to return the emphasis to the soil based on experiments that used approaches with little application to the real world.…”
Section: The Possible Mechanisms By Which Plants Sense a Drying Soilmentioning
confidence: 99%